2021
DOI: 10.3389/fimmu.2021.788185
|View full text |Cite
|
Sign up to set email alerts
|

ASCVac-1, a Multi-Peptide Chimeric Vaccine, Protects Mice Against Ascaris suum Infection

Abstract: Control of human ascariasis, the most prevalent neglected tropical disease globally affecting 450 million people, mostly relies on mass drug administration of anthelmintics. However, chemotherapy alone is not efficient due to the high re-infection rate for people who live in the endemic area. The development of a vaccine that reduces the intensity of infection and maintains lower morbidity should be the primary target for infection control. Previously, our group demonstrated that immunization with crude Ascari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…In addition, this model has been used to unravel the mechanisms explaining how Ascaris infections may induce or exacerbate allergic inflammation by assessing the impact of the cross‐reactivity between allergens and Ascaris antigens in the allergic effector response, as well as in the mediated resistance to helminths. Recently, investigating the interface between Ascaris infection and pulmonary allergic inflammation induced by house dust mite (HDM), we identified Ascaris ‐encoded tropomyosin and enolase as the two major HDM homologues based on high sequence and structural similarity (Gazzinelli‐Guimaraes, Bennuru, et al., 2021). We showed that the HDM‐triggered IgE cross‐reactive antibodies were functional as they mediated immediate hypersensitivity responses in skin testing.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this model has been used to unravel the mechanisms explaining how Ascaris infections may induce or exacerbate allergic inflammation by assessing the impact of the cross‐reactivity between allergens and Ascaris antigens in the allergic effector response, as well as in the mediated resistance to helminths. Recently, investigating the interface between Ascaris infection and pulmonary allergic inflammation induced by house dust mite (HDM), we identified Ascaris ‐encoded tropomyosin and enolase as the two major HDM homologues based on high sequence and structural similarity (Gazzinelli‐Guimaraes, Bennuru, et al., 2021). We showed that the HDM‐triggered IgE cross‐reactive antibodies were functional as they mediated immediate hypersensitivity responses in skin testing.…”
Section: Commentarymentioning
confidence: 99%
“…2021), and finally as an important tool for preclinical vaccine trials (Castro et al, 2023;Gazzinelli-Guimaraes et al, 2018;Gazzinelli-Guimaraes, Nogueira, et al, 2021;Wei et al, 2017), because it allows the evaluation of infection-driven pathogenesis as well as vaccine-driven immunogenicity at a tissue level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation